Residue retention and minimum tillage improve physical environment of the soil in croplands: A global meta-analysis - Li, Yuan; Li, Zhou; Cui, Song; Jagadamma, Sindhu; Zhang, Qingping (Soil & tillage research, 2019)
•A global meta-analysis on soil physical properties under conservation tillage.•Conservation tillage has higher aggregate size, stability and available water capacity.•Increased bulk density under conservation tillage remains non-harmful for crop growth.•Soil pH decreased under conservation tillage.•The response of soil physical properties vary with experiment duration. Conservation tillage practices, here defined as no-tillage (NT) or reduced tillage (RT) with/without residue retention, have been widely used to alleviate the negative effects caused by intensive tillage practices. Implementing effective and sustainable agriculture requires a deeper understanding of the impacts of conservation tillage practices on soil physical properties. This study examined the effects of conservation tillage practices on soil physical properties, including soil bulk density, aggregate size and stability, hydraulic properties, and soil pH; based on data collected from 264 studies published worldwide since 1980. The results indicated that no-tillage (NT), NT with residue retention (NTS), and reduced tillage (RT) increased bulk density by 1.4, 2.6, and 2.1%, respectively, compared with conventional tillage (CT). Soil bulk density decreased by 2.9% in NTS compared with NT, and 3.9% in RT with residue retention (RTS) compared with RT. The effect size of bulk density significantly decreased with the increasing experimental duration under NT and NTS practices. Compared to CT, conservation tillage practices increased aggregate mean weight diameter (MWD), geometric mean weight diameter and water stable aggregate (WSA) regardless of the residue retention or minimum tillage systems. The largest effect size of MWD (51.9%) and WSA (54.9%) appeared under NTS as compared to the CT. The effect size of MWD and WSA increased under NT with the increasing experimental duration. NT increased saturated hydraulic conductivity by 24.6% compared to CT. All conservation tillage practices increased soil available water capacity (AWC) compared with CT and NTS with a 10.2% increase in AWC compared with NT. The effect size of AWC increased under RT and NT practices with the increasing experimental duration. Soil pH decreased by 1.7 and 1.0% under RTS compared with RT and CT, respectively; and NT led to a 2.8% reduction in soil pH compared with CT. The effect size of soil pH decreased under RT and NT treatments with the increasing experiment duration. Overall, conservation tillage practices positively affected many soil physical properties; and the extent of the effects varied with the duration of the experiment.